Ethyl acetate fraction of Cola hispida leaf protects against doxorubicin-induced myocardial injury in male albino rats - Chiemeka Lynda Umenwanne; Martins Obinna Ogugofor; Obioma U. Njoku (SpringerOpen, 2021)
Abstract Background Cardiovascular diseases have continued to be the leading cause of death globally. In addition, some of the drugs used in the treatment of the diseases present some adverse effects which limit the usefulness of such drugs. Thus, there is a need for novel drugs whose side effect is either minimal or non-existent. The presence of bioactive compounds in Cola hispida leaf is of great significance in the treatment and management of cardiovascular conditions. This study investigated the cardio-protective potential against doxorubicin (Dox)-induced cardiac infarction in rats. Results Dox induction resulted to muscle fiber degeneration in Dox-treated rats hence revealed significant (p < 0.05) elevation in the serum level of cardio biomarker enzymes and lipid peroxidation profile while significant (p < 0.05) fall in cardiac enzymatic antioxidant levels were observed relative to the normal control. Pre-treatment with ethyl acetate fraction of Cola hispida leaf expressed cardio-protective potentials against Dox-induced cardiotoxicity by significantly (p < 0.05) lowering the levels of cardiac biomarker enzymes towards normal, building up the activities of subdued antioxidant enzymes and depleting its malondialdehyde level. Histopathology photomicrograph of the heart tissues expressed myxomatous degeneration but was ameliorated through the administration of the fraction. Conclusion In accordance with the findings from this study, the administration of ethyl acetate fraction of Cola hispida leaf is effective against Dox-induced redox imbalance due to its enriched antioxidant phytoconstituents.